Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

(*) if tan( pie/4 + theta) + tan (pie/4 – theta)= a then tan cube (pie/4 + theta) + tan cube(pie/4-theta) =

(*)
if tan( pie/4 + theta) + tan (pie/4 – theta)= a then tan cube (pie/4 + theta) + tan cube(pie/4-theta) =

Grade:11

1 Answers

Nishant Vora IIT Patna
askIITians Faculty 2467 Points
6 years ago
Hello student, Please find the answer to your question below

tan( pie/4 + theta) + tan (pie/4 – theta)= a
(1+tanØ)/(1- tanØ) + (1-tanØ)/(1+tanØ) = a
=> a = 4tanØ/ (1 – tan2Ø)
From here you can find out tanØ
once you get tanØ ….you can get tan( pie/4 + theta) and tan (pie/4 – theta)

Then put in the required equation

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free